2015
DOI: 10.1371/journal.pone.0137752
|View full text |Cite
|
Sign up to set email alerts
|

Nowcasting Intraseasonal Recreational Fishing Harvest with Internet Search Volume

Abstract: Estimates of recreational fishing harvest are often unavailable until after a fishing season has ended. This lag in information complicates efforts to stay within the quota. The simplest way to monitor quota within the season is to use harvest information from the previous year. This works well when fishery conditions are stable, but is inaccurate when fishery conditions are changing. We develop regression-based models to “nowcast” intraseasonal recreational fishing harvest in the presence of changing fishery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…It already appears that angler apps can replace some aspects of conventional surveys (Jiorle 2015;Papenfuss et al 2015), and similar results have been found for online social media and Internet search volume (Carter et al 2015). Although it is important to integrate with 'business-as-usual' approaches, angler apps are likely to render some conventional approaches obsolete, or at least consign them to supporting roles such as validation or calibration.…”
Section: Fisheries Integrationmentioning
confidence: 60%
See 1 more Smart Citation
“…It already appears that angler apps can replace some aspects of conventional surveys (Jiorle 2015;Papenfuss et al 2015), and similar results have been found for online social media and Internet search volume (Carter et al 2015). Although it is important to integrate with 'business-as-usual' approaches, angler apps are likely to render some conventional approaches obsolete, or at least consign them to supporting roles such as validation or calibration.…”
Section: Fisheries Integrationmentioning
confidence: 60%
“…Although it is important to integrate with 'business-as-usual' approaches, angler apps are likely to render some conventional approaches obsolete, or at least consign them to supporting roles such as validation or calibration. It already appears that angler apps can replace some aspects of conventional surveys (Jiorle 2015;Papenfuss et al 2015), and similar results have been found for online social media and Internet search volume (Carter et al 2015). We must also be open to a new science and management paradigm that is relatively datarich, enlightened, nimble and user-defined.…”
Section: Fisheries Integrationmentioning
confidence: 71%
“…Available data are often obtained with methods that are resource intensive (e.g., creel surveys; random telephone surveys; Pollock et al, 1994;Board and Council, 2006;Hartill et al, 2012;Rocklin et al, 2014;Hartill and Edwards, 2015;Zarauz et al, 2015;Bellanger and Levrel, 2017;Holdsworth et al, 2018;Hyder et al, 2018;van Poorten and Brydle, 2018). As a complement to more traditional methods, less resource-demanding data sourced from digital applications and social media platforms are attracting increasing attention (Martin et al, 2014;Carter et al, 2015;Venturelli et al, 2017). However, it remains unclear to what extent such data can produce reliable insights of use in management and monitoring of recreational fisheries.…”
Section: Introductionmentioning
confidence: 99%
“…iEcology and conservation culturomics are particularly interesting in the context of recreational fisheries because of the many people that are involved in this activity, of which a sizable fraction uses digital platforms on the internet. New monitoring and assessment methods tailored towards recreational fishing have been developed to collect and analyze data from digital platforms (e.g., Carter et al, 2015;Martin et al, 2014;Monkman et al, 2018b;Sbragaglia et al, 2019a;Venturelli et al, 2017). For example, digital information of catches by recreational fishers constitutes a widespread spatio-temporal network of samples that -if appropriately analyzed -can provide an unprecedented body of information, especially for aquatic environments where sampling is constrained across time and space.…”
Section: Introductionmentioning
confidence: 99%